Manajemen Lingkungan dalam Menurunkan Penyakit Infeksi pada Balita terhadap Kejadian Stunting di Kabupaten Solok - Sari Arlinda; Sri Lestari Adriyanti; Muklis; Suksmerri; Lindawati (Jurnal Pengabdian Masyarakat Cendikia Jenius, 2024)
West Sumatra is a province that has access to clean drinking water sources and access to proper sanitation below the Indonesian average, namely 68.83% and 52.77%, which is the sixth lowest. One of the districts that is high is Solok Regency. One of the sub-districts that is very densely populated and very heterogeneous and with a high incidence rate in Solok Regency is Kubung District, which consists of 2 Puskesmas working areas, namely Salayo Puskesmas and Tanjung Bingkung Puskesmas. The purpose of this activity is to provide knowledge of environmental management in reducing infectious diseases in toddlers against stunting to the community, cadres and sanitarians. The activity method is counseling and providing pocket books and pretest and posttest questionnaire sheets to measure community knowledge about how to manage the environment to prevent stunting. Results: there was an increase after being given counseling where 76.7% of the community already had a clean water source. The availability of toilets was 80% and 70% already used septic tanks. Conclusion: It is important to implement sanitation management in community life to prevent infectious diseases in toddlers due to poor sanitation, which can reduce the incidence of stunting in toddlers.